The cognitive and neural organisation of speech processing - Patti Adank (Frontiers Research Topics, 2016)
Speech production and perception are two of the most complex actions humans perform. The processing of speech is studied across various fields and using a wide variety of research approaches. These fields include, but are not limited to, (socio)linguistics, phonetics, cognitive psychology, neurophysiology, and cognitive neuroscience. Research approaches range from behavioural studies to neuroimaging techniques such as Magnetoencephalography, electroencephalography (MEG/EEG) and functional Magnetic Resonance Imaging (fMRI), as well as neurophysiological approaches, such as the recording of Motor Evoked Potentials (MEPs), and Transcranial Magnetic Stimulation (TMS). Each of these approaches provides valuable information about specific aspects of speech processing. Behavioural testing can inform about the nature of the cognitive processes involved in speech processing, neuroimaging methods show where (fMRI and MEG) in the brain these processes take place and/or elucidate on the time-course of activation of these brain areas (EEG and MEG), while neurophysiological methods (MEPs and TMS) can assess critical involvement of brain regions in the cognitive process. Yet, what is currently unclear is how speech researchers can combine methods such that a convergent approach adds to theory/model formulation, above and beyond the contribution of individual component methods? We expect that such combinations of approaches will significantly forward theoretical development in the field. The present research topic comprise a collection of manuscripts discussing the cognitive and neural organisation of speech processing, including speech production and perception at the level of individual speech sounds, syllables, words, and sentences. Our goal was to use findings from a variety of disciplines, perspectives, and approaches to gain a more complete picture of the organisation of speech processing. The contributions are grouped around the following five main themes: 1) Spoken language comprehension under difficult listening conditions; 2) Sub-lexical processing; 3) Sensorimotor processing of speech; 4) Speech production. The contributions used a variety of research approaches, including behavioural experiments, fMRI, EEG, MEG, and TMS. Twelve of the 14 contributions were on speech perception processing, and the remaining two examined speech production. This Research Topic thus displays a wide variety of topics and research methods and this comprehensive approach allows an integrative understanding of currently available evidence as well as the identification of concrete venues for future research.